Teachers' Communication Strategy in Enhancing Learning in Islamic Education Subject at Private Junior High School Annysa, Deli Serdang District - Ulandari, Dindah; Basri, Hasan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to examine the communication strategies employed by Islamic Education (PAI) teachers to enhance the effectiveness of learning at SMP Annysa. Effective communication between teachers and students is crucial in delivering values and learning materials optimally. This research uses a qualitative approach with a phenomenological research type. Data collection techniques were conducted through interviews, observations, and documentation. Data analysis techniques employed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings of this study indicate that teachers use effective communication strategies, such as verbal and nonverbal communication, to enhance students' learning motivation. The impact of teacher communication on students' learning motivation is also significant, as effective communication can increase students' self-confidence and motivate them to learn. Teachers also develop communication skills through personal approaches, the use of supportive media, and constructive feedback. The results of this study can serve as a reference for teachers to improve their communication skills and students' learning motivation.